(3CKQ GdTQjYI GdESdGejI Ydi GdfXe GdbGfhfjI hGdGLJeGYjI aj ChQhHG GdZQHjI NdGd GdYUhQ GdhSWi (B/ s - (3MSGe GdOjf eOMJ eMeO TGcQ s; (3eMehO GdSbGs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI,s, 2010)
(3fXQG ddJYUH GdOjfj GdPj SGO aj ChQhHG (B- (3aj GdYUhQ GdhSWi (B- (3hGdPj GSJJHY YLR GdcKjQjf Yf GdEbQGQ HCf GdTQjYI GdESdGejI cGf dgG GdaVd Ydi GdfXe GdbGfhfjI hGdGLJeGYjI GdChQhHjI aj Pdc GdReGf eOYjf CfgG GdSHH aj LehO GdYGde GdESdGej hJQGLYg(B: (3JeKd gOa GdOQGSI aj eMGhdI EHQGR eGcGf ddTQjYI GdESdGejI ef OhQ aj bjGOI GdYGde GdESdGej aj GdYUhQ GdhSWi(B: (3hCf JCKjQgG bO GeJO Edi ZQH ChQhHG cLRA ef JCKjQ GdMVGQI GdESdGejI Ydjg, hCf SHH GdJQGLY GdPj CUGH GdYGde GdESdGej de jcf cGefG aj GdTQjYI GdESdGejI PGJgG, Hd EfgG JSJWjY bjGOI GdYGde GdESdGej ddfghV eQI CNQi(B.s
(3CWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI, cdjI GdMbhb, bSe adSaI GdbGfhf hJGQjNg (B2010.s
(3HHdjhLQGajG(B: (3UaMGJ (B233-241.s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdESdGejs; (3GdTQjYI GdESdGejI s; (3GdfXe GdbGfhfjI s; (3GdbGfhfj GdChQhHjs; (3GdJLGQI GdOhdjIs; (3GdbGfhf GdChQhHjs; (3GdNQGaGJ s; (3GdYUhQ GdhSWi s; (3ChQhHG GdZQHjIs; (3GdMQhH GdUdjHjI s; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3adSaI GdbGfhfs